Vascularização foliar e a identificação de espécies de Eugenia L. (Myrtaceae) da bacia hidrográfica do Rio Tibagi, PR - Cardoso, Cristiano M. V. [UNESP]; Sajo, Maria das Graças [UNESP] (Sociedade Botânica de São Paulo, 2004)
Com o objetivo de reconhecer caracteres vegetativos que auxiliem na identificação de Myrtaceae, foram estudadas as folhas de 17 espécies de Eugenia, presentes da bacia do Rio Tibagi, PR. Analisando os padrões de nervação das lâminas e as características da bainha perivascular, na região do pecíolo, foi possível separar essas espécies em três grupos distintos. O padrão camptódromo-broquidódromo ocorre em nove espécies; o acródromo em quatro espécies e, nas quatro restantes, observa-se um padrão misto. A bainha perivascular do pecíolo pode ser de natureza parenquimática, esclerenquimática ou mista. Elaborou-se uma chave de identificação usando esses caracteres vegetativos, demonstrando que eles podem, seguramente, auxiliar na identificação das espécies de Eugenia.

With the objective of recognizing vegetative helpfull characteristics in the Myrtaceae identification, we studied the leaf anatomy of 17 species of Eugenia, from the bank of Tibagi river, State of Paraná. Using leaf blade venation and, the pattern of the petiole vascular bundle sheaths we separated the species in three different groups. The camptodromous-brochidodromous venation pattern occur in nine species, the acrodromous pattern in four species, and a mixed pattern in four species. Depending on the species, the petiole vascular bundle sheaths can be of parenchymatous, sclerenchymatous or mixed nature. A dicotomic identification key was elaborated with these vegetative characters showing that they can surely aid in the Eugenia species identification.
Vasculature and identification of Eugenia (Myrtaceae) from the bank of Tibagi river, State of Paraná
Keywords: Eugenia; Myrtaceae; nervação foliar; Eugenia; leaf venation; Myrtaceae